A new view of the lethal apoptotic pore. - Gorka Basañez; Lucian Soane; J Marie Hardwick (PLoS Biology, 2012)
Cell death by apoptosis is indispensable for proper development and tissue homeostasis in all multicellular organisms, and its deregulation plays a key role in cancer and many other diseases. A crucial event in apoptosis is the formation of protein-permeable pores in the outer mitochondrial membrane that release cytochrome c and other apoptosis-promoting factors into the cytosol. Research efforts over the past two decades have established that apoptotic pores require BCL-2 family proteins, with the proapoptotic BAX-type proteins being direct effectors of pore formation. Accumulating evidence indicates that other cellular components also cooperate with BCL-2 family members to regulate the apoptotic pore. Despite this knowledge, the molecular pathway leading to apoptotic pore formation at the outer mitochondrial membrane and the precise nature of this outer membrane pore remain enigmatic. In this issue of PLOS Biology, Kushnareva and colleagues describe a novel kinetic analysis of the dynamics of BAX-dependent apoptotic pore formation recapitulated in native mitochondrial outer membranes. Their study reveals the existence of a hitherto unknown outer mitochondrial membrane factor that is critical for BAX-mediated apoptotic pore formation, and challenges the currently popular view that the apoptotic pore is a purely proteinaceous multimeric assembly of BAX proteins. It also supports the notion that membrane remodeling events are implicated in the formation of a lipid-containing apoptotic pore.